Pendekatan Konseling Realitas Dalam Mengatasi Sibling Rivalry Anak Usia Dini - Alivia Zahra; Ati Kusmawati; Fitria Anggraheni Subagio; Maulana Nadzif Fanany Putra Hanafi (Institut Nalanda, 2024)
This article aims to determine the sibling rivalry in early childhood in the concept of a reality counseling approach and theresults of previous relevant research on sibling rivalry. Sibling rivalry is a form of competition between sibling,between brothers and sisters to win the attention and affection of parents. Every child has a unique personality and has different needs. This literature review discusses sibling rivalry behavior that occurs in early childhood in the concept of theory and reality counseling. This research employed descriptive qualitative method using a literature review. The results of this research ofl iterature indicate that thea pplication of reality counseling can reduce sibling rivalry behavior in early childhood